RAGAM PENDEKATAN PENELITIAN KUANTITATIF DAN KUALITATIF SERTA TAHAPAN DALAM PENELITIAN - Deassy Aretya Saksitha; Risnita; M.Syahran Jailani; Sofwatillah (LPPM Universitas Cipta Mandiri, 2024)
Research aims to find problems, solve problems and develop new knowledge. Research can reveal the truth scientifically with research methods. The research method is a planned, systematic, scientific, and rational way to collect facts. This study aims to examine in depth the various approaches in scientific research. The object of the research discussion is a qualitative and quantitative. The research method chosen by the author is a systematic literature review. In this study, researchers examined in depth the concepts and applications of various research approaches in various previous scientific studies. Materials for research studies are theoretical studies and the results of previous research from books, national journals, and international journals. The author uses data analysis with a descriptive qualitative approach. The results of the research show that the use of methods in scientific research has been able to discover new truths and knowledge for the development of knowledge that is beneficial to human life. The use of research methods encourages comprehensive and holistic problem-solving.